Classification of Zakat Fitrah Recipients Using Naïve Bayes Method - R Dimas Adityo (Fakultas Teknik Universitas Bhayangkara, 2020)
Indonesia is a country with a majority Muslim population. In the daily life of the Indonesian population, it is inseparable from the influences of Islamic teachings. In life in this world there are many commands of Allah that must be carried out, including the order to pay zakat. One of them is when Eid al-Fitr is required to pay zakat fitrah for each of its citizens. In grouping the distribution of zakat fitrah using the Naïve Bayes classification method. Naïve Bayes classification itself is a classification method that can be applied in classification. The classification system used to classify categories of zakat fitrah recipients. From each test results using test data and training data randomly, and each test using training data which increased 37 pieces of data in each test. It can be concluded that the more training data the level of accuracy decreases. The determination of the amount of training data and test data is very influential on the final results of calculations using the Naïve Bayes method. Class determination also affects the final results of calculations using this Naïve Bayes method.